2021
DOI: 10.1073/pnas.2024828118
|View full text |Cite
|
Sign up to set email alerts
|

An epithelial Nfkb2 pathway exacerbates intestinal inflammation by supplementing latent RelA dimers to the canonical NF-κB module

Abstract: Aberrant inflammation, such as that associated with inflammatory bowel disease (IBD), is fueled by the inordinate activity of RelA/NF-κB factors. As such, the canonical NF-κB module mediates controlled nuclear activation of RelA dimers from the latent cytoplasmic complexes. What provokes pathological RelA activity in the colitogenic gut remains unclear. The noncanonical NF-κB pathway typically promotes immune organogenesis involving Nfkb2 gene products. Because NF-κB pathways are intertwined, we asked whether … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…However, p100 also dimerizes with RelB as a precursor of non-canonical NF-κB ( 69 ), which is utilized by the NIK signaling downstream of LTβR, preventing the inhibitory effect of p100 as well as enhancing the non-canonical NF-κB signaling and finally forming a positive loop to maintain proinflammatory responses to counter bacteria ( 67 ). In agreement with previous findings, a recent publication reported that non-canonical NF-κB signaling enhanced canonical RelA mediated inflammatory responses in IECs and exacerbated colitis ( 70 ). They also revealed an upregulated non-canonical NF-κB signaling in IBD patients, indicating that uncontrolled IEC-specific NIK signaling involves in the pathogenesis and progression of IBD ( 70 ).…”
Section: Nik In Intestinal Immunity and Homeostasissupporting
confidence: 92%
See 3 more Smart Citations
“…However, p100 also dimerizes with RelB as a precursor of non-canonical NF-κB ( 69 ), which is utilized by the NIK signaling downstream of LTβR, preventing the inhibitory effect of p100 as well as enhancing the non-canonical NF-κB signaling and finally forming a positive loop to maintain proinflammatory responses to counter bacteria ( 67 ). In agreement with previous findings, a recent publication reported that non-canonical NF-κB signaling enhanced canonical RelA mediated inflammatory responses in IECs and exacerbated colitis ( 70 ). They also revealed an upregulated non-canonical NF-κB signaling in IBD patients, indicating that uncontrolled IEC-specific NIK signaling involves in the pathogenesis and progression of IBD ( 70 ).…”
Section: Nik In Intestinal Immunity and Homeostasissupporting
confidence: 92%
“…In agreement with previous findings, a recent publication reported that non-canonical NF-κB signaling enhanced canonical RelA mediated inflammatory responses in IECs and exacerbated colitis ( 70 ). They also revealed an upregulated non-canonical NF-κB signaling in IBD patients, indicating that uncontrolled IEC-specific NIK signaling involves in the pathogenesis and progression of IBD ( 70 ). In physiological state, intestinal inflammatory response is self-limiting rather than fulminant due to the negative regulatory function of NIK signaling.…”
Section: Nik In Intestinal Immunity and Homeostasissupporting
confidence: 92%
See 2 more Smart Citations
“…Yilmaz et al showed that lymphotoxin beta (LTβ), a stimulus of the non-canonical signaling pathway, can induce simultenaous processing of p100 and p105 possibly from the p105/p100 heterocomplexes. In a recent publication, Chawla et al also demonstrated simultaneous processing of p105 and p100 through non-canonical signaling generating p50:RelA and p52:RelA complexes in intestinal epithelial cells ( Chawla et al, 2021 ). Thus, a variety of NF-κB dimers can arise from the processing of p105, p100 and p105/p100 kappaBsomes in a stimulus specific manner.…”
Section: Generation Of P52/nf-κb2 From P100mentioning
confidence: 99%